The Role of Motivation, Activeness, and Numeracy Skills on Grade X Vocational High School Students’ Mathematics Learning Achievement - Aulia, Syifa Rahma; Rejeki, Sri (Journal of Medives : Journal of Mathematics Education IKIP Veteran Semarang, 2023)
This study aims to analyze and describe the contribution of learning motivation, learning activeness, and numeracy skills on vocational high school students' mathematics learning achievement. This quantitative research involves a population of grade X students at a private vocational high school in Surakarta, Central Java, Indonesia, Academic Year 2022/2023. With the quota sampling technique, 45 students were obtained as the research sample. The data-collecting method applied is questionnaires and tests. The data were analyzed using multiple linear regression tests with a significance level of 5% using SPSS software. The normality, linearity, multicollinearity, autocorrelation, and heteroscedasticity tests were performed as prerequisite analysis tests. Based on the results of data analysis, it can be concluded that: (1) There is a significant contribution of learning motivation to student learning outcomes with a partial determination coefficient of 14.77, (2) There is no significant contribution of active learning to student learning outcomes, with a partial determination coefficient of 3.21. (3) There is no significant contribution from numeracy skills to student learning outcomes, with a partial determination coefficient of 0.01, (4) there is a significant contribution of learning motivation, learning activeness, and numeracy skills on vocational high school students mathematics learning achievement with a simultaneous determination coefficient ( ) of 0.18. It means that the percentage of contribution given by learning motivation, learning activeness, and numeracy skills on vocational high school students mathematics learning achievement is 18%. In comparison, other factors outside this study influence the remaining 82%. Keywords : learning motivation, learning activeness, numeracy skills, and mathematics learning achievement .